A Review Paper on Slit Erosion (International Journal of Innovative Research in Computer Science & Technology, 2022)
The eruptive wearing of hydrokinetic  blades is a complex operation impacted by a number of  elements such as silt size, softness and concentrations,  flow speed, and foundation materials properties. As  eruptive attrition and eventual breakdown of hydroelectric  plants grows, the performance of the generator decreases.  The bulk of research studies were done on tiny specimens  in different kinds of test rigs to replicate the flow behaviour in the turbines, but real fluid properties and the phenomena  of crack growth are too complicated to model. The present  essay examines the work of many academics in this field  in depth. Depending on a literary review, many aspects of  silt eroding in hydraulic generators, separate causes for  decreasing wind turbines quality and reliability, and  relevant remediation strategies provided by different  experts have been discussed.
Keywords: Erosion; Hydropower; Slit; Thermal; Turbine